Secure Software Architecture and Design: Security Evaluation for Hybrid Approach - Qurashi, Jameel Ahmad; Singh, Harvir; Nunia, Vijay (International Journal of Computer Sciences and Engineering, 2019)
Software furnishes administrations that may accompany a few vulnerabilities or risks. Attackers perform activities that break the security of framework through dangers and cause disappointment. To dodge security helplessness, there are numerous security- explicit ideas that ought to be resolved as prerequisites amid software improvement life cycle so as to convey solid and secure software. This paper first, studies various existing procedures, systems required for creating secure software dependent on the related distributed works. It begins by displaying the most important Secure Software Development Lifecycle, a correlation within the primary security highlights for each procedure is proposed. The consequences of the examination will give the software engineer with a rule which will help in choosing the best secured process. Second, the paper lists a lot of the most broadly utilized determination dialects with the points of interest and impediments for each.